â€œThe new modernâ€: The subjective motivation for wearing a veil in a Muslim-majority city, Langsa, Aceh - Fitria, Syiva; Siregar, Mawardi; Sembiring, Masdalifah (Institut Agama Islam Negeri Langsa, 2023)
The veil-wearing is debated in various non-Muslim countries, yet it is indispensable to explore the veil-wearing in Muslim-majority country that upholds the ideology of religious moderation. Despite the fact that Langsa City implements Sharia law, women who wear veils encounter discrimination. While wearing veil, women are confronted with obstacles, but still preserve the veil. Thus, analysing the motive and the maintaining factor is crucial. This study investigates why people choose to wear and continue wearing veils. The current study is a qualitative study with an ethnographic approach. Data was collected using observations, in-depth interviews and Focus Group Discussions (FGD) with 10 informants selected purposively. The results analysis revealed that the use of the veil does not happen suddenly but through a complex process. The motivation for wearing a veil is a spiritual force. However, other multi-factor underlines the decision to wear one. The factors are dedication to religious principles, protecting oneself, following one spouse's advice, and a desire to appear fashionable but yet respectful and Islamic. This study implies that there is a shift in perspectives regarding the veiling practice as a means of spirituality as well as a means of self-expression. Moreover, Islamic veils transcend Islamic regulations because women wear them for diverse purposes.